2007
DOI: 10.1890/06-1751.1
|View full text |Cite
|
Sign up to set email alerts
|

Flightlessness and the Energetic Cost of Wing Molt in a Large Sea Duck

Abstract: Although the replacement of feathers apparently represents the major event of somatic production in the annual cycle of wild birds, knowledge about the energetics of molt has always been hampered by logistical and technical difficulties, which are exacerbated by the fact that birds are able to compensate behaviorally to buffer any variation in energy demand. During wing molt, sea ducks (Mergini) and other diving birds lose all of their wing feathers at once, leading to a period of temporary flightlessness of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 48 publications
1
75
0
Order By: Relevance
“…As in many other bird species (e.g. Klaassen 1995;Guillemette et al 2007), the process of moult in the Common Snipe has been shown to be energetically costly. Young snipe were found to have lost more than 50% of their fat reserves during the postjuvenile moult (Minias et al 2010b), and depletion of endogenous fat was accompanied by a significant decrease in plasma concentrations of triglycerides during the advanced stage of moult (Podlaszczuk et al 2017).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…As in many other bird species (e.g. Klaassen 1995;Guillemette et al 2007), the process of moult in the Common Snipe has been shown to be energetically costly. Young snipe were found to have lost more than 50% of their fat reserves during the postjuvenile moult (Minias et al 2010b), and depletion of endogenous fat was accompanied by a significant decrease in plasma concentrations of triglycerides during the advanced stage of moult (Podlaszczuk et al 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Nutritional costs of moult are primarily associated with increased amino acid metabolism necessary for renewal of feathers, as well as with increased heat loss caused by reduced insulation (Lindström et al 1993;Klaassen 1995;Portugal et al 2007). Feather production results in a deposition of proteins that constitute up to 25% of lean body mass (Murphy and Taruscio 1995), and this process is associated with substantial increase of metabolic rate (Croxall 1982;Guillemette et al 2007). Also, flight-feather moult may impose additional energetic costs resulting from reduced flight performance (Swaddle and Witter 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Molt migration commenced when birds left the breeding location and ceased when birds arrived at the molt location. In the few instances when the molt location was not McKinley Bay in the year after marking, we identified the molt location as the area where birds were located for [28 days between mid-to late July and most of August and the distance between locations was \20 km (Guillemette et al 2007). Distances travelled during migratory periods were calculated by summing the distances between locations for the respective periods but should be considered minimum distances as ducks did not travel in a straight line between points.…”
Section: Definitions Of Migratory Periodsmentioning
confidence: 99%
“…At higher latitudes, seasonal variations in photoperiod elicit changes in avian physiology associated with energetically costly behaviours such as migration, egg-laying, incubation, wing moult and feather production (Piersma et al 2003;Guillemette et al 2007;Portugal and Guillemette 2011;. Furthermore, changes in climate may influence predation pressures, resource acquisition and thermoregulation, which may affect energy expenditure (Weathers and Sullivan 1993).…”
Section: Introductionmentioning
confidence: 99%